Element and Water-Soluble Vitamins Profile of Rhus coriaria L. (Sumac) Grown in Different Regions - Ali, Haval Mohammed; Karatas, Fikret; Ozer, Dursun; Saydam, Sinan (Springernature, 2024)
In this study, the amounts of some elements and water-soluble vitamins in Rhus coriaria L. (Sumac) samples grown in different regions were analyzed by ICP-OES and HPLC, respectively. The maximum amount of Na, K, Mg, and P was determined in the sumac samples of Kadana, Sheladize, Maras, and Derishke regions, respectively. The richest regions in terms of trace elements such as Zn, Cu, Fe, Se, Mn, Cr, Mo, Ni, and B were Charput, Derishke, Ranya, Charput, Ranya, Derishke, Elazig, Derishke, and Kadana, respectively. The highest amount of As, Cd, Pb, and Hg in sumac samples were determined in Kadana, Kadana, Trawanish, and Charput regions, respectively, while the lowest amounts were determined in Maras, Sheladize, Elazig, and Trawanish regions sumac samples. Since target hazard coefficient (THQ) and total target hazard coefficient (TTHQ) values calculated for minor, toxic and heavy metals investigated in sumac samples are well below one; therefore, they do not pose a health risk. From the result obtained, sumac is a good food additive spice in terms of water-soluble vitamins except ascorbic acid. The amounts of ascorbic acid, thiamine, riboflavin, nicotine amide, nicotinic acid, pantothenic acid, pyridoxine, folic acid, and cyanocobalamin in sumac samples varied between 78.90-36.57, 173.57-61.11, 518.4-182.3, 314.0-105.6, 1292.1-788.7, 779.2-301.7, 385.8-133.4, 826.2-473.1, and 192.6-73.9 mu g/g dw, respectively. Differences in the amount of elements and water-soluble vitamins among sumac samples from different regions may be due to geographical and ecological reasons.
Keywords: Sumac (Rhus coriaria L.); Elements; Vitamins; ICP-OES; HPLC